Georgia Architectural and Historic Properties Survey of 710 Jackson Street, Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 710 Jackson Street, Valdosta, Ga. One story double pen house with gabled tin roof, shiplap siding. Shed porch. Double hung sash windows with 2/2 lights. Fair condition. Date of Construction: App. 1900-1910. Typical double pen house - has significance as part of a potential N.R. district.
1 electronic record and derivatives. 1 PDF. 3 scans. 84.6 MB (88,771,036 bytes). 1 photograph digitized from original negative. 2400 DPI TIF. 300 DPI 4x6 JPG.
Keywords: Electronic records; Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)